Reduced admixture of North Atlantic Deep Water to the deep central South Pacific during the last two glacial periods. (14th June 2016) - Molina‐Kescher, Mario; Frank, Martin; Tapia, Raúl; Ronge, Thomas A.; Nürnberg, Dirk; Tiedemann, Ralf
Abstract: The South Pacific is a sensitive location for the variability of the global oceanic thermohaline circulation given that deep waters from the Atlantic Ocean, the Southern Ocean, and the Pacific Basin are exchanged. Here we reconstruct the deep water circulation of the central South Pacific for the last two glacial cycles (from 240, 000 years ago to the Holocene) based on radiogenic neodymium (Nd) and lead (Pb) isotope records complemented by benthic stable carbon data obtained from two sediment cores located on the flanks of the East Pacific Rise. The records show small but consistent glacial/interglacial changes in all three isotopic systems with interglacial average values of −5.8 and 18.757 for ε Nd and 206 Pb/ 204 Pb, respectively, whereas glacial averages are −5.3 and 18.744. Comparison of this variability of Circumpolar Deep Water (CDW) to previously published records along the pathway of the global thermohaline circulation is consistent with reduced admixture of North Atlantic Deep Water to CDW during cold stages. The absolute values and amplitudes of the benthic δ 13 C variations are essentially indistinguishable from other records of the Southern Hemisphere and confirm that the low central South Pacific sedimentation rates did not result in a significant reduction of the amplitude of any of the measured proxies. In addition, the combined detrital Nd and strontium ( 87 Sr/ 86 Sr) isotope signatures imply that Australian and New Zealand dust has remained the principal contributor of lithogenic material to the central South Pacific. Key Points: Little deep water circulation changes in the past 240, 000 years in the central South Pacific Reduced North Atlantic Deep Water admixture during glacials to the Southern Ocean South Pacific lithogenic material mainly sourced from SE Australia and South New Zealand